Pengaruh Economic Value Added dan return On Equity (ROE) Terhadap Harga Saham pada perusahaan Investasi yang Terdaftar Di BEI Tahun 2016-2019. - Winny Lian Seventeen; Seftya dwi shinta (Universitas Prof.Hazairin,SH Bengkulu, 2021)
This study aims to examine the effect of Economic Value Added (EVA) and Return On Equity (ROE) on Stock Prices in Investment Companies Listed on the IDX in 2016-2019.” This research is an explanatory quantitative research. Sources of secondary data obtained through literature studies, documentation, books, magazines, newspapers, written archives related to the object to be studied. The results showed that 60.9% of the stock price variable was influenced by the EVA variable and the ROE variable. Simultaneous test results explain that EVA and ROE variables have an effect on stock prices. The results of the partial test explain that the EVA variable has no effect on stock prices, while the ROE variable has an influence on stock prices.